Influence of Particle Additives on the Lubricated Tribology of Aluminium Metal Matrix Composite - Singh, ParamPreet (My University, 2017)
Aluminium composite because of their improved mechanical properties, low density, better corrosion resistance and low production cost are very much suitable for various applications in the field of automotive, aerospace and marine industries. From the past and till the present scenario, it is evident that the research work on aluminium metal matrix composites (AMMC) is primarily focused on the fabrication and mechanical characterization. The potential tribological behaviors of these composites are mainly evaluated through dry sliding friction and wear testing. In this research work, in addition to the dry sliding test, an attempt has been made to investigate the effect of oil and oil additives on the sliding wear and friction behavior of aluminium composite. Three different types of composites were fabricated by stir casting method and their mechanical and metallurgical properties are investigated. Hardness characterization of the composites is done to evaluate the interfacial bonding between reinforcement and matrix. Metallurgical properties are studied using SEM and EDS to evaluate the distribution of particles and probabilities of defects. Then these composites are examined for their tribological characteristics under dry and lubricated contact with steel. The most tribologically favored pair is then subjected to the particle based lubrication for further enhancement of tribological response against the selected counterpart. The friction and wear property of the fabricated composites sliding against EN31 disk are investigated under dry, lubricated base oil SN 500 but without additive and lubricated with base oil in the presence of particle additives such as boric acid, MWCNT and MoS2. The outcome of this thesis works shows that there is a significant influence of suitably selected particle based additives on the wet tribology of composite. Starting with various types of composite-steel tribopairs and dry sliding condition, the present work, tries to design a tribo-material package for an improved tribological response under the given operating condition. From our study CNT and boric acid emerged out as potential additives for the tribological applications of Al-B4C composites.
Master of Engineering -Producation
Keywords: AMMC; Stir Casting; Additives; Wet tribology; Characterization